Aplikasi Rute Tujuh Puncak Gunung Indonesia Berbasis Mobile - Bambang Santoso; Feby Ryandika (Program Studi Teknik Informatika Universitas Pamulang, 2021)
Mountain climbing is a chalenging sport. It is a healthy sport, both physically and mentally. However, this sport has many challenging sides. For one, they have to have really fit bodies. They need to walk a very long distance, many times on difficult and dangerous tracks, like steep and slippery roads, with deep cliffs on the sides. Other than that, they need to be able to help themselves. When they are in the middle of climbing, they cannot get help. The inhibitants are rare in such difficult-to-reach places. Therefore it is dangerous when climbers get lost in the mountains. They cannot ask directions, and cannot seek help. This application intends to provide information about climbing routes, directions, visiting points that they can stay, and the distance to reach the peak and estimated walking time. With a map that is easy to use, climbers can prepare the things they need to carry. The application contains routes for seven mounts. These seven mounts are on seven islands in Indonesia. For each island, we pick the highest mount which we call the summit in that island. Seven summits in this application are mount Kerinci in Sumatera island, mount Semeru in Jawa island, mount Rinjani in Nusa Tenggara islands, mount Bukit Raya in Kalimantan island, mount Latimojong in Sulawesi island, mount Binaiya in Maluku islands, and mount Cartenz Pyramid in Papua island. The application is intended to be used for climbers who plan to climb one of these Indonesia's summits.